2019
DOI: 10.1186/s12903-019-0914-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dental experience on a dental implant navigation system

Abstract: Background This study evaluated the operating performance of an implant navigation system used by dental students and dentists of prosthodontic background with varying levels of experience. A surgical navigation system and optical tracking system were used, and dentists’ accuracies were evaluated in terms of differences between the positions of actually drilled holes and those of the holes planned using software before surgeries. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Therefore, we could examine the effect of the demographics of the dentist on the accuracy of static guided implant surgery. For dynamic computer-guided navigation systems, junior dentists or dental students were reported to have better performance in terms of the accuracy of implant placement [26,27]; However, we did not find similar studies for the static guided implant surgery in the literature. The effect of age on the accuracy of static guided implant surgery remains an issue to be clarified.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, we could examine the effect of the demographics of the dentist on the accuracy of static guided implant surgery. For dynamic computer-guided navigation systems, junior dentists or dental students were reported to have better performance in terms of the accuracy of implant placement [26,27]; However, we did not find similar studies for the static guided implant surgery in the literature. The effect of age on the accuracy of static guided implant surgery remains an issue to be clarified.…”
Section: Discussionmentioning
confidence: 59%
“…Figure 2 shows the complete flowchart of the study selection process. Of the 24 articles, 10 reported on clinical studies involving humans [43][44][45][46][47][48][49][50][51][52] and 14 reported on preclinical "in vitro" studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The types of studies included for each system can be observed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…When we analyzed the different surgeons in the dynamic navigation group, we found that there was no statistical difference in the influence of different experience levels of the surgeons on accuracy. Sun et al proved that the implant navigation system could help a dentist to insert the implant into the correct position accurately, without the influence of the operational experience [21]. Rungcharassaeng et al compared experienced with inexperienced surgeons in the accuracy of dental supported static surgical guide templates, and the results showed no significant difference [22].…”
Section: Discussionmentioning
confidence: 99%